Missing the Mark: Insolvency Set-Off and the Case of CeDe Group v KAN: Case note on ECJ 21 November 2019, C‑198/18, ECLI:EU:C:2019:1001 (CeDe Group/KAN) - Schuijling, Ben (European Insolvency and Restructuring Journal, 2021)
Article 4 EIR, which states the main rule that the law of the Member State where insolvency proceedings are opened is applicable to the proceedings and their effects, must be interpreted as not applying to an action brought by the liquidator of an insolvent company established in one Member State for the payment of goods delivered under a contract concluded before the insolvency proceedings were opened in respect of that company, against the other contracting company, which is established in another Member State